#### Answer

$a=\dfrac{y-3}{2-b}$

#### Work Step by Step

$\bf{\text{Solution Outline:}}$
To solve the given equation, $
y=2a-ab+3
$ for $
a
,$ use the Distributive Property and the properties of equality to isolate the variable.
$\bf{\text{Solution Details:}}$
Using the Distributive Property which is given by $a(b+c)=ab+ac,$ the expression above is equivalent to
\begin{array}{l}\require{cancel}
y=2a-ab+3
\\\\=
y=a(2-b)+3
.\end{array}
Using the properties of equality to isolate the variable, the equation above is equivalent to
\begin{array}{l}\require{cancel}
y=a(2-b)+3
\\\\
y-3=a(2-b)
\\\\
\dfrac{y-3}{2-b}=\dfrac{a(2-b)}{2-b}
\\\\
\dfrac{y-3}{2-b}=a
\\\\
a=\dfrac{y-3}{2-b}
.\end{array}